Introduction in: Modlitewnik królowej Bony 1521-1528. Facsimile. - Wójcik, Rafał (Wydawnictwo Poznańskie Studia Polonistyczne, 2016)
This file contains an introduction to the facsimile edition of the prayer book belonging to the queen Bona Sforza, wife of Sigismund I the Elder. The illuminations in the prayer book have been made in a workshop of Stanisław Samostrzelnik, the most famous book illuminator in Poland of the 16th century.
Keywords: prayer book; Renaissance; Bona Sforza; Stanisław Samostrzelnik; history of book; illuminations; history of spirituality; Jagiellons dynasty